Obesity Resistance Promotes Mild Contractile Dysfunction Associated with Intracellular Ca2+ Handling - Santos de Sa, Felipe Goncalves dos; Lima-Leopoldo, Ana Paula; Jacobsen, Bruno Barcellos; Togneri Ferron, Artur Junio; Estevam, Wagner Muller; Salome Campos, Dijon Henrique [UNESP]; Castardeli, Edson; Holanda da Cunha, Marcia Regina; Cicogna, Antonio Carlos [UNESP]; Leopoldo, Andre Soares (Arquivos Brasileiros Cardiologia, 2015)
Background: Diet-induced obesity is frequently used to demonstrate cardiac dysfunction. However, some rats, like humans, are susceptible to developing an obesity phenotype, whereas others are resistant to that. Objective: To evaluate the association between obesity resistance and cardiac function, and the impact of obesity resistance on calcium handling. Methods: Thirty-day-old male Wistar rats were distributed into two groups, each with 54 animals: control (C; standard diet) and obese (four palatable high-fat diets) for 15 weeks. After the experimental protocol, rats consuming the high-fat diets were classified according to the adiposity index and subdivided into obesity-prone (OP) and obesity-resistant (OR). Nutritional profile, comorbidities, and cardiac remodeling were evaluated. Cardiac function was assessed by papillary muscle evaluation at baseline and after inotropic maneuvers. Results: The high-fat diets promoted increase in body fat and adiposity index in OP rats compared with C and OR rats. Glucose, lipid, and blood pressure profiles remained unchanged in OR rats. In addition, the total heart weight and the weight of the left and right ventricles in OR rats were lower than those in OP rats, but similar to those in C rats. Baseline cardiac muscle data were similar in all rats, but myocardial responsiveness to a post-rest contraction stimulus was compromised in OP and OR rats compared with C rats. Conclusion: Obesity resistance promoted specific changes in the contraction phase without changes in the relaxation phase. This mild abnormality may be related to intracellular Ca2+ handling.
Keywords: Obesity-Resistance; High-Fat Diet; Cardiac Function; Ca2+ Handling; Rats